Solvency Test in Polish Simple Joint-Stock Company: A Review and Comparative Analysis - Herbet, Andrzej; Wielgat, Natalia (Review of European and Comparative Law, 2021)
The subject of the article is a comparative analysis of the solvency test - a legal instrument that conditions causa societatis payments for limited liability companies upon ascertaining their impact on its future liquidity (ability to pay debts as they come due), which has recently been incorporated into the Polish legal system with reference to a simple joint-stock company (pol. Prosta Spółka Akcyjna) (Article 30015 § 5 of Polish Commercial Companies Code). Considering that the solvency test originated in common law, the comparative analysis of the instrument in question was set against the background of selected foreign legal systems, i.e., the law of New Zealand, United States and the United Kingdom, where the solvency test is shaped much differently than the polish one.